2-Chloro-N-[N-(4-chlorobenzoyl)hydrazinocarbothioyl]benzamide - Ali, Hapipah Mohd; Yamin, B.M.; Sahali Mardi, A.; Khamis, N.A.; Sukeri Yusof, M. (International Union of Crystallography, 2004)
The title compound, C15H11Cl2N 3O2S, has a similar structure and similar structural dimensions to the unsubstituted N-(N-benzoylhydrazinocarbothioyl)benzamide. However, the presence of Cl atoms at the para and ortho positions in the benzamide and benzoyl groups, respectively, caused the dihedral angle between these groups to increase from 16.42 (14)° in the unsubstituted compound to 74.96 (8)°. The molecule is stabilized by intermolecular C-H⋯O and N-H⋯S interactions, forming polymeric chains parallel to the c axis. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.